Francophone African cinema : history, culture, politics and theory - Frindéthié, Martial Kokroa (Jefferson, N.C. : McFarland, 2009)
"This book offers a transnational and interdisciplinary analysis of 16 Francophone African films studied in the context of transnational conversations between African filmmakers and conventional theorists. It examines black French filmmakers' treatments of a number of cross-cultural themes, including intercontinental encounters and reciprocity, ideology and subjective freedom, governance and moral responsibility, sexuality and social order, and globalization"--Provided by publisher.
Introduction: engaging African cinema -- "There is no conversation here, my boy": spectral returns of Fanon and Hegel in Bassek Ba Kobhio's The great white man of Lambaréné -- The language you govern in: the rise and fall of the African despot in Balufu Bakupa Kanyinda's Le damier: Papa national oyé and Cheick Oumar Sissoko's Guimba the tyrant -- Nostalgic memories and nomadic spirits: Merzak Allouache's Bab-el-oued and Karim Dridi's Bye-bye -- Allegorizing the quest for autonomy: Cheick Oumar Sissoko's Finzan and Amadou Seck's Saaraba -- Writing the soxual order: Ousmane Sembåne's Faat Kiné and Ngangura Mweze's La vie est belle -- Cogito must have gone crazy: construction and/as deconstruction of masculinity in Nouri Bouzid's Bent familia and Mufida Tlatli's The silences of the palace -- Keita: the heritage of the griot: economic, social, and cultural organization of ancient Africa -- Crisis in French Africa as hexagonal possibility: globalization à la françiaise -- "There is no trade going on there": tales from the killing fields of the Congo -- Conclusion.
Bibliografija: str. 247-251. - Kazalo
Keywords: Motion pictures -- Africa, French-speaking.; Motion pictures -- Social aspects -- Africa, French-speaking.; Motion pictures -- Political aspects -- Africa, French-speaking.; Culture conflict in motion pictures; Africa -- In motion pictures; film - Afrika - frankofone zemlje; društveni aspekit - Afrika, frankofone zemlje; kulturni konflikt na filmu